The Luke Commentary Collection : An All-In-One Commentary Collection for Studying the Book of Luke /: An All-In-One Commentary Collection for Studying the Book of Luke. (2016) - Bock, Darrell L; Garland, David E; Liefeld, Walter L; Pao, David W
No abstract available